Different Training Modalities Improve Energy Cost and Performance in Master Runners - Pugliese, Lorenzo; Porcelli, Simone; Vezzoli, Alessandra; La Torre, Antonio; Serpiello, Fabio R.; Pavei, Gaspare; Marzorati, Mauro (Frontiers in Physiology, 2018)
PURPOSE: The aim of this study was to compare the effects of continuous moderate-intensity and discontinuous high-intensity training on running performance in master runners. METHODS: Thirty-four male master runners (47.2 ± 7.4 years) were assigned to three different groups: continuous moderate-intensity training (CMIT), discontinuous high-intensity training (DHIT), and control group (CON). CMIT and DHIT performed 8-week of supervised training (3 session∙wk-1; 35 km∙wk-1) while CON maintained their normal training habits (3-4 session∙wk-1; 50 km∙wk-1). Peak oxygen consumption (V┴˙O2peak) and peak running speed (vpeak) during incremental treadmill exercise, gas exchange threshold (GET), speed at GET, energetic cost of running (Cr), and 5-km performance were evaluated before and after training. RESULTS: Following the training period, both CMIT and DHIT significantly reduced Cr (-4.4% and -4.9%, respectively, P<0.05), increased speed at GET (3.4% and 5.7%, P<0.05) and improved 5-km time-trial performance (3.1% and 2.2%, P<0.05) whereas no differences were found for V┴˙O2peak and GET (as %V┴˙O2peak). After training, vpeak improved only for DHIT (6%, P<0.05). No differences were found in any variable for CON. CONCLUSIONS: This study indicates that both CMIT and DHIT may positively affect running performance in middle-aged master runners. This improvement was achieved despite a significant reduction of the amount of weekly training volume.